Studi Integrasi Seed Coating Fe dan Inkubasi Pupuk Organik Limbah Sagu dalam Pengoptimalan Pertumbuhan Padi: Study on the Integration of Fe Seed Coating and Sago Waste Organic Fertilizer Incubation for Optimizing Rice Growth - Fadhila, Emmy; Rasyid, Burhanuddin; Jayadi, Muh. (Universitas Hasanuddin, 2024)
Rice (Oryza sativa) production in Indonesia has declined due to low iron (Fe) availability in alkaline soils, impacting plant growth and yield. Integrating Fe seed coating with sago (Metroxylon sp.) waste organic fertilizer may improve Fe availability and soil quality, offering a potential solution to enhance rice production. Our objective was to examine the effects of Fe seed coating and the incubation of sage waste organic fertilizer on rice growth. The study employed a factorial 2-factor randomized block design. The first factor was the concentration of Fe seed coating, with four levels: 0 g, 55 g with 2.5 g gypsum, 110 g with 5 g gypsum, and 275 g with 12.5 g gypsum. The second factor was the incubation time of organic fertilizer, with four durations: 0 weeks, 3 weeks, 4 weeks, and 5 weeks. The interaction between Fe seed coating and sago waste organic fertilizer incubation significantly impacted plant height (153.33 cm), leaf color chart scale (4), chlorophyll a (254.73 μmol.m-2), chlorophyll b (96.90 μmol.m-2), with the most notable effects observed at a Fe seed coating concentration of 275 g with 12.5 g of gypsum and a 5-week incubation period. The application of Fe seed coating at a concentration of 275 g with 12.5 gypsum, combined with a 5-week of sago waste organic fertilizer, effectively enhances plant height, chlorophyll a, chlorophyll b, and the leaf color chart scales.